When AI Becomes an Agent of the Firm: Examining the Evolution of AI in Organizations Through an Agency Theory Lens - Humberd, Beth K.; Latham, Scott F. (Journal of Management Studies, 2026)
Abstract Our work begins with the premise that the integration of artificial intelligence (AI) into firm decision making parallels the emergence of the professional manager, which prompted the birth of agency theory. We examine the evolution of AI through an agency theory lens, considering how the nature of firm control and decision rights change as AI evolves. While AI will initially mimic human routines, we theorize a point at which the AI system will achieve a level of autonomy and self‐determination to be considered an agent of the firm. How, then, can we align an agent with the fate of the firm, when that agent is no longer a human? To address this, we integrate agency theory with a model of AI evolution, demonstrating that conflict between an AI agent and the firm will require a reconsideration of agency mechanisms if agent‐principal alignment is to be achieved. We theorize specific forms of monitoring and incentive alignment that serve to align an AI agent with the firm's interests, thus extending agency mechanisms in the context of AI. Our theoretical exercise offers important implications for scholarship at the intersection of AI and organizational theory, as well as considerations for practice and policy.